Impact of individualism and collectivism over the individual's technology acceptance behaviour: A multi-group analysis between Pakistan and Turkey. Issue 6 (12th October 2015) - Abbasi, Muhammad Sharif; Tarhini, Ali; Elyas, Tariq; Shah, Farwa
Abstract : Purpose: – The purpose of this paper is to develop an extended model of technology acceptance to include behavioural beliefs (perceived usefulness and perceived ease of use), subjective norms, management support (at institutional and governmental levels) to examine the academics' internet acceptance behaviour within the Pakistan and Turkish context. In addition to this, impact of cultural dimension individualism-collectivism (IC) is also examined on the basis of moderator construct. Design/methodology/approach: – Data were collected from 380 academics' using a cross-sectional survey. Data were analysed using structural equation modelling (partial least squares) in conjunction with multiple group analysis. Findings: – The results revealed that proposed model achieved acceptable fit with the data (i.e. R 2=39 per cent in intention) and most of the hypothesised relationships were supported. The results also revealed that culture showed a moderating effect on hypothetical relationships. Specifically, the effects of management support were stronger for the respondents having high on collectivist society (i.e. Pakistan). Originality/value: – The study is useful in non-western cultural contexts. Specifically, in contrast to previous studies, diversity of individuals' acceptance behaviour is examined in Turkey and Pakistan. Additionally, this study had examined moderating impact of cultural dimension (i.e. IC) over academic's behavioural intention to accept the internet technology.